Let's solve your equation step-by-step.<span><span><span>x−<span>(<span><span>9x</span>−10</span>)</span></span>+11</span>=<span><span><span>12x</span>+20</span>−2</span></span>Step 1: Simplify both sides of the equation.<span><span><span>x−<span>(<span><span>9x</span>−10</span>)</span></span>+11</span>=<span><span><span>12x</span>+20</span>−2</span></span><span>Simplify: (Hide steps)</span><span><span><span><span><span>x+</span>−<span>9x</span></span>+10</span>+11</span>=<span><span><span><span>12x</span>+20</span>+</span>−2</span></span><span><span><span>(<span>x+<span>−<span>9x</span></span></span>)</span>+<span>(<span>10+11</span>)</span></span>=<span><span>(<span>12x</span>)</span>+<span>(<span>20+<span>−2</span></span>)</span></span></span>(Combine Like Terms)<span><span><span>−<span>8x</span></span>+21</span>=<span><span>12x</span>+18</span></span><span><span><span>−<span>8x</span></span>+21</span>=<span><span>12x</span>+18</span></span>Step 2: Subtract 12x from both sides.<span><span><span><span>−<span>8x</span></span>+21</span>−<span>12x</span></span>=<span><span><span>12x</span>+18</span>−<span>12x</span></span></span><span><span><span>−<span>20x</span></span>+21</span>=18</span>Step 3: Subtract 21 from both sides.<span><span><span><span>−<span>20x</span></span>+21</span>−21</span>=<span>18−21</span></span><span><span>−<span>20x</span></span>=<span>−3</span></span>Step 4: Divide both sides by -20.<span><span><span>−<span>20x</span></span><span>−20</span></span>=<span><span>−3</span><span>−20</span></span></span><span>x=<span>320</span></span>Answer:<span>x=<span>3<span>20</span></span></span>
#11 is 2 ounces because there are 16 ounces in 1 pound and if u add all the #rs you get 32, divide by 16 and u get 2.
#12 is 10 ounces because when u add the #rs up u get 54. u subtract that from 64 because that's how many ounces are in 4 pounds, so ur answer is 10
Answer:
f(x)= -(x+1)^2 -2
Step-by-step explanation:
f(x)=(x-h)^2 +k; (h,k)
Then you would substitute the x and y of the coordinate and solve.
-6= -(1+1)^2 -2
-6= -(4) -2
-6 = -6
Answer:
The equation given to us is in the Standard form
y
=
a
x
2
+
b
x
+
c
where
a
=
1
,
b
=
0
and
c
=
−
1
The Axis of Symmetry is given by the formula
x
=
−
b
2
a
x
=
−
0
2
⋅
1
x
=
0
is the Axis of Symmetry of the Parabola with the equation
y
=
x
2
−
1
Step-by-step explanation:
Answer:
no solution
Step-by-step explanation:
10x-83-4x=6x
combine like terms
6x-83=6x
cross the equal sign
-83=0
aka no solution